León Tornero, S.J. and Lorenzo Montúfar GR ∴ 33: Religious drama and anticlericalism in Costa Rica (19th century) - Marín Guzmán, Roberto (2026)
This article examines the figure of Father León Tornero, S.J., his Daniel, Biblical Drama in Five Acts, and his controversy with the liberal Freemason Lorenzo Montúfar during the nineteenth century. Through the analysis of Tornero’s drama and polemical writings, it highlights the role of Jesuit literature as a defense of the Church amid the rise of liberal anticlericalism in Central America. The study situates Tornero’s literary production within the ideological tensions of his time, revealing how his work blends faith, rhetoric, and pedagogy to uphold spirituality against the challenges of secular modernity.